Body image, satisfaction with sexual life, self-esteem, and anxiodepressive symptoms: A comparative study between premenopausal, perimenopausal, and postmenopausal women. (2nd January 2019) - Séjourné, Natalène; Got, Fabrice; Solans, Catherine; Raynal, Patrick
ABSTRACT: Menopause is an important life transition in women, and it is associated with significant physical and psychological changes. This study aimed at examining how the menopausal transition influences body image and satisfaction with sexual life. To this aim, body image dissatisfaction, sexual dissatisfaction, and self-esteem were compared in three groups of women with distinct menopausal status (premenopausal n = 142, perimenopausal n = 66, or postmenopausal n = 149), while controlling for depressive and anxiety symptoms and BMI. Using ANOVA between these three groups, we observed that dissatisfaction with body image was significantly higher in the perimenopausal sample compared with its premenopausal counterpart. In the postmenopausal sample, body image improved, as this group displayed body image scores close to the premenopausal level. In addition, sexual dissatisfaction was significantly increased in the perimenopausal and postmenopausal samples, which is compatible with the concept that higher body appreciation positively predicted sexual function. We conclude that body image dissatisfaction reaches a maximum during the perimenopausal phase, before returning to a level nearly identical between the premenopausal and the postmenopausal phases.